IDENTIFICATION OF VESSEL ARRIVAL NUMBER AND FISH CATCH AT NUSANTARA FISHING PORT (PPN) IN MERAUKE - Mappasessu, Baso; Dumatubun, Nelly F.M.L.; Rumbino, Viceriani (Departemen PSP IPB, 2025)
One of the efforts in sustainable fisheries management is to measure fishing capacity. Fishing capacity is the maximum number of fish caught by a fishing fleet in a certain period. Currently, Merauke Nusantara Fisheries Port (PPN) is a type B fishing port that functions as a center for fisheries activities, including recording the number of ship arrivals and fish catches. Republic of Indonesia Fisheries Management Area (WPP-RI) 718, which includes the waters of the Arafura Sea, has abundant fish resource potential. However, using these resources must be carried out sustainably to avoid over-exploitation which can harm the fisheries ecosystem and the fishermen's economy. One of the efforts in sustainable fisheries management is to measure fishing capacity. Catching capacity is the maximum number of fish caught by a fishing fleet in a certain period. Currently, there is no comprehensive estimate of fishing capacity in WPP-RI 718, especially in PPN Merauke, which is at risk of not being in line with the Code of Conduct for Responsible Fisheries guidelines. The process of determining fishing capacity begins with identifying fishing activities. This study analyzes the number of vessels, gross tonnage (GT), and the volume of catches landed at the Nusantara Fisheries Port of Merauke Regency. Data was collected through direct observation at the Nusantara Fisheries Port (PPN) and supported by observation, interview, and literature study methods. The respondents targeted in this study were captains or owners of fishing units. The results of the study showed that the number of fishing vessels landing their catches at the Merauke Nusantara Fisheries Port (PPN) in the period from March to May reached 348 units. The vessels consisted of 320 units measuring less than 30 GT and 28 units measuring more than 30 GT. In addition, 22 types of fish were identified with a total catch landed reaching 682.5 tons. Key words: catch, fishing boat, identification, Merauke, Nusantara Fisheries Port